(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Health is indeed an important factor for the development of the economy thus the health sector of the economy is an important sector which cannot be neglected. The economy of MP is growing gradually over the years but is this growing economy catering the needs of the poor people? There has been high mortality infant rate Inspite of the growth the poorest of the poor is striving for better health condition .The health care is not available & affordable to all. Our paper is trying to analysis the extent of inclusiveness in the Public Health Sector of Madhya Pradesh.Growth implies participation in the process of growth and also sharing of benefit from growth. Inclusive state institutions are a necessary pre condition to fighting poverty in a sustainable way. But for state institutions to be inclusive, they first have to be effective, accountable, and representative. Thus inclusive growth is both an outcome and a process. On the one hand, it ensures that everyone can participate in the growth process, both in terms of decision making for organizing the growth progression as well as in participating in the growth itself. On the other hand, it makes sure that everyone shares equitably the benefits of growth. In fact, participation without benefit sharing will make growth unjust and sharing benefits without participation will make it a welfare outcome. The importance of inclusive growth is well acknowledged among the policy makers.